3D team leadership : a new approach for complex teams - Kirkman, Bradley Lane; Harris, T. Brad (Stanford Business Books, an imprint of Stanford University Press, 2017)
To create a fuller portrait of team behavior, this book introduces an innovative, ""3-D"" framework that takes into account the individuals who make up a team, the subgroups that form within and between teams, and the team as a whole. Delivering practical guidance rooted in scholarship, this is a thoughtful and straightforward guide.